PENGARUH KENDALA KEUANGAN TERHADAP TAX AVOIDANCE: PERAN DEWAN DIREKSI WANITA DAN INDEPENDENT COMMISSIONERS SEBAGAI PEMODERASI: THE INFLUENCE OF FINANCIAL CONSTRAINTS ON TAX AVOIDANCE: THE ROLE OF FEMALE ON BOARDS AND INDEPENDENT COMMISSIONERS AS MODERATIONS - Nurmah, Rahmawati Yulijah; Silfi, Alfiati; Hanif, Rheny Afriana (Universitas Riau, 2024)
Companies use tax avoidance as a tactic to reduce the amount of taxes they must pay. In the meanwhile, taxes are income that needs to be collected as much as feasible by the state. According to agency theory, tax evasion is the result of disparities in interests between businesses and the government. In response to the problem of tax evasion, this study is to investigate and evaluate the impact of financial limitations on tax evasion, taking into account moderating factors such as the presence of female directors and independent commissioners in manufacturing businesses listed between 2018 and 2022 on the Indonesian Stock Exchange. Purposive sampling was the sampling strategy employed in this study, which produced a sample of 76 businesses. Using the IBM SPSS Statistics 25 program, multiple linear regression analysis and moderated regression analysis are the data analysis techniques employed for each moderating variable. The test results involving the control factors (profitability, leverage, firm size, and number of commissioners on the board) indicate that tax evasion is impacted by each of the control variables. The study's findings demonstrate that tax evasion is influenced by financial limitations. Then, financial restrictions that are controlled by independent commissioners and women on boards have an impact on tax evasion.